Aplicação de IOT em cadeia de suprimentos no setor de telecomunicações - Soares, Rogério de Almeida (2020)
Digital technology enables companies to obtain information about their production lines and services, allowing them to better understand their operation. This understanding enables the development of actions related to the client, since it allows the company to quickly adapt to changes in scenarios. The capture of this information is carried out through technologies that seek to bring the physical and digital worlds together, such as the Internet of Things (IoT). The fact of connecting machines between themselves and the internet, also provides visibility, agility and adaptability applicable to the supply chain. So it is a solution that contributes to the improvement and the search for efficiency in the production line. In this sense, this research sought to identify which technologies are related to the IoT that can influence the supply chain of a telecommunications company to offer a better operational performance from the perspective of the organization. Faced with a gap in the literature on the pillars: technology, processes, products and people, and in addition to the cut in the supply chain of a telecommunications company, a qualitative research was chosen. This research used the presentation of a case study and semi-structured interviews with employees of a telecommunications company, directly linked to the supply chain and the IoT technology area. The research allowed to identify the stage that the organization is in relation to the contribution of the operations area to obtain operational advantage and to the organizational strategy, from the perspective of PROCESSES AND STRATEGY, before a real case of application of IoT in Supply Chain in Telecommunications. It also demonstrates that it can be a tool to help the organization to better understand its internal competences, and to evaluate those that can be developed with the use of new technologies, evidencing even those considered most relevant in the search for operational efficiency, from the perspective PEOPLE. It was also up to this research to propose solutions, through the application of technology, its prioritization and contribution aiming at a greater efficiency of the operation under the TECHNOLOGY perspective. As a technological product, the research proposed to develop a technical solution, using IoT to effect the changes in the processes of the supply chain and also generating KPI's for monitoring and management. Thus, the research made some academic and empirical contributions, encouraging the conduct of future studies on the IoT theme in service providers.